2017
DOI: 10.1080/14767058.2017.1326898
|View full text |Cite
|
Sign up to set email alerts
|

Is nitric oxide an essential mediator in cervical inflammation and preterm birth?

Abstract: These studies show that LPS increases the expression of the iNOS in an animal model of preterm birth, but the nitric oxide metabolites nitrate and nitrite do not initiate the pro-inflammatory LPS-induced breakdown of the cervical epithelial barrier.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
0
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 31 publications
2
0
0
Order By: Relevance
“…Moreover, we observed that EE exposure reduced the effects of LPS on cervical PGE2 production, thus contributing to the prevention of pathological cervical softening and preterm labor. We also observed an LPS-induced increase of cervical iNOS expression in our model, consistent with previous reports regarding the participation of this pro-inflammatory mediator in preterm birth (Törnblom et al 2005, Nold et al 2018. Similarly to previous reports (Aranda et al 2019), we observed that EE exposure prevented LPS induction of cervical NOS activity in our model.…”
Section: Discussionsupporting
confidence: 93%
“…Moreover, we observed that EE exposure reduced the effects of LPS on cervical PGE2 production, thus contributing to the prevention of pathological cervical softening and preterm labor. We also observed an LPS-induced increase of cervical iNOS expression in our model, consistent with previous reports regarding the participation of this pro-inflammatory mediator in preterm birth (Törnblom et al 2005, Nold et al 2018. Similarly to previous reports (Aranda et al 2019), we observed that EE exposure prevented LPS induction of cervical NOS activity in our model.…”
Section: Discussionsupporting
confidence: 93%
“…Of importance to note, as previously mentioned, macrophages have the capabilities to produce nitric oxide and prostaglandins. Inhibition of nitric oxide or prostaglandins synthesis suppresses cervix softening and ripening while stimulation of nitric oxide production or prostaglandin treatment advance remodeling and induce preterm birth in rats (125), mice (83,126), and women (127). These findings collectively support the conclusion that nitric oxide and prostaglandins are a critical part of the common mechanism for birth at term and with preterm birth.…”
Section: Schema For Cervix Transformation From Soft To Ripe To Dilatisupporting
confidence: 59%